TEOREMA TITIK TETAP PADA RUANG NORM-n STANDAR - Shelvi Ekariani; Hendra Gunawan (Jurusan Matematika FMIPA Universitas Jenderal Soedirman, 2012)
On the standard n-normed space,i.e an inner product space equipped with the standard n-norm, one can derive a norm from the n-norm in a certain way. The purpose of this note is to establish the equivalence between such a norm and the usual norm on standard n-normed space. Further, this fact together with others use to prove a fixed point theorem on the standard n-normed space.